The Application of Problem-Based Learning Model to Improve Students’ Mathematical Problem-Solving Skills in Junior High School - Andreas P Peranginangin (SEAN Institute, 2025)
This qualitative study investigates the application of the Problem-Based Learning (PBL) model to enhance mathematical problem-solving skills among junior high school students. PBL is a student-centered approach that uses real-world, open-ended problems to drive learning, emphasizing collaboration, critical thinking, and self-directed study. Through observations, interviews, and document analysis in a junior high school setting, this research provides a comprehensive understanding of how PBL implementation impacts students' abilities to solve complex mathematical problems. Findings demonstrate that PBL effectively fosters improved problem-solving strategies, deeper conceptual understanding, and greater student engagement. This study supports integrating PBL as a viable pedagogical model for mathematics education at this level.